Practical ethics for psychologists : a positive approach (Washington, DC, US : American Psychological Association, 2006)
(from the cover) Psychologists confront ethical dilemmas each day. Practical Ethics for Psychologists: A Positive Approach helps psychologists clarify what they value, consider how they should behave, and determine what constitutes proper professional conduct. This book is unique in stressing the importance of positive ethics--that is, ways in which psychologists can reach their highest ethical ideals, rather than just avoiding breaking rules. Using the 2002 Ethics Code of the American Psychological Association as a guide, the authors lay out a five-step model for resolving ethical dilemmas, illustrating the discussion with thumbnail sketches of both ethical and questionable behaviors. Throughout, they stress the importance of self-care, which involves self-regulation, emotional competence, and an understanding of the unique occupational challenges of being a psychologist. Readers will find themselves consulting the book over and over again for guidance on dealing with ethically complex issues like competence, multiple relationships, informed consent, confidentiality (including confidentiality with life-endangering patients), fees and financial issues, public statements, and risk management. Individual chapters are devoted to special issues for psychologists working in forensics, teaching, assessment, therapy, and supervision and training. This book is ideal for classroom use or self-study.
Research and scholarship Samuel J. Knapp and Leon D. VandeCreek / 231-249
Keywords: profesionalna etika; profesionalni standardi